Գոյականի առկայացման քերականական կարգը արդի հայերէնում․ որոշեալութեան եւ անորոշութեան ենթակարգեր - Աւետիսեան, Եուրի (տպ. Atlas)
The semantic aspects of the grammatical category of occurrence and the forms of grammatical expression have often undergone changes during the historical development of the Armenian language. That is why they have often become the subject of examination and discussion in Armenian grammars. The question was addressed more or less thoroughly by M. Abeghyan, H. Acharyan, S. Abrahamyan, G. Jahukyan, M. Asatryan, H. Petrosyan, H. Cholakyan, A. Yeghiayan and others. A large amount of work has been done, a very detailed and thorough examination has been made. However, we believe that certain classification points and principles need to be reviewed and reformulated today. This study is aimed at that goal.
Keywords: Հայ լեզուաբանութիւն; Քերականութիւն